Emotional Intelligence of Students Based on Birth Order - Fitniwilis Fitniwilis; Fatma Nofriza; Ema Nurulita (Jurnal Neo Konseling, 2022)
This study aims to determine the differences in students' emotional intelligence based on birth order, namely the eldest child and the youngest child. The approach in this research is a comparative descriptive approach with descriptive analysis. The sample in this study was 231 Muhammadiyah 4 Jakarta high school students with 122 eldest children and 109 youngest children. The instrument used is the BarOn EQ-i_YV (Emotional Quation Inventory Young Version) developed by Reuven. Data analysis used independent samples t test with SPSS 25. The results showed that there was a significant difference between students' emotional maturity based on the birth order of the eldest and youngest children.